2012
DOI: 10.1111/apm.12015
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic archaea in subgingival sites: a review

Abstract: Archaea are non-bacterial prokaryotes associated with oral microbiota in humans, but their roles in oral pathologies remain controversial. Several studies reported the molecular detection of methanogenic archaea from periodontitis, but the significance of this association has not been confirmed yet. An electronic search was therefore conducted in MEDLINE-Pubmed to identify all papers published in English connecting archaea and periodontal infections. Data analysis of the selected studies showed that five gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 48 publications
4
60
0
3
Order By: Relevance
“…This human archaeal commensal has a highly restricted energy metabolism (Fricke et al, 2006), which makes it a specialized member of the gastrointestinal microbiome. Archaea have been shown to be ubiquitous members of the adult GIT microbiome (Dridi et al, 2009), were sporadically detected in the vaginal environment (Belay et al, 1990), and were shown to colonize the skin surface (Probst et al, 2013) and the oral cavity (Nguyen-Hieu et al, 2013). As the presence of archaea was also apparent in CSD infants and also in samples collected at day 1 in our study, we can postulate that transmission paths besides vaginal transmission, such as fecal-oral, oral-oral, or by skin contact most probably occur perinatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This human archaeal commensal has a highly restricted energy metabolism (Fricke et al, 2006), which makes it a specialized member of the gastrointestinal microbiome. Archaea have been shown to be ubiquitous members of the adult GIT microbiome (Dridi et al, 2009), were sporadically detected in the vaginal environment (Belay et al, 1990), and were shown to colonize the skin surface (Probst et al, 2013) and the oral cavity (Nguyen-Hieu et al, 2013). As the presence of archaea was also apparent in CSD infants and also in samples collected at day 1 in our study, we can postulate that transmission paths besides vaginal transmission, such as fecal-oral, oral-oral, or by skin contact most probably occur perinatally.…”
Section: Discussionmentioning
confidence: 99%
“…Archaea have been sporadically detected in the vaginal environment before, although exclusively in women with bacterial vaginosis (Belay et al, 1990). As archaea are mainly inhabitants of the human GIT, but also colonize the skin surface (Probst et al, 2013) as well as the oral cavity (Nguyen-Hieu et al, 2013), a transfer from mother to infant by fecal-oral or oral-oral route seems thereby most probable.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Archaea domain have also been described in the subgingival biofilm (reviewed in [86]). Methanobrevibacter oralis phylotypes SBGA-1 and SGBA-2 are detected in a subset of severe periodontitis patients who harbor low levels of Treponema spp [87].…”
Section: Periodontal Microbiome and Immunitymentioning
confidence: 99%
“…In a recent review, Nguyen-Hieu et al pooled the data from several studies of methanogens in the oral cavity and concluded that M . oralis is significantly associated with periodontal disease both in terms of abundance comparisons between patients and controls and between diseases and healthy sites within the same patient [50]. Furthermore, they concluded that indirect evidence supports the contribution of that methanogen to periodontal disease and that this contribution likely stems from syntrophic interactions with sulfate-reducing bacteria.…”
Section: Subgingival Archaeamentioning
confidence: 99%
“…oralis [52] and, thus, suppression of M . oralis could contribute to its efficacy [50]. Statins that inhibit the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductases of eukaryotes and archaea lower blood cholesterol in humans, but they also effectively inhibit archaeal growth because they block the synthesis of their main membrane lipids [53].…”
Section: Subgingival Archaeamentioning
confidence: 99%